Interleukin-6-174G > C (rs1800795) polymorphism distribution and its association with rheumatoid arthritis: A case-control study and meta-analysis. (3rd April 2017) - Dar, Sajad Ahmad; Haque, Shafiul; Mandal, Raju Kumar; Singh, Taru; Wahid, Mohd; Jawed, Arshad; Panda, Aditya K.; Akhter, Naseem; Lohani, Mohtashim; Areeshi, Mohammed Yahya; Rai, Gargi; Datt, Shyama; et al.
Abstract: The association of interleukin-6 (IL-6)-174G > C (rs1800795) single nucleotide polymorphism (SNP) with the risk of acquiring rheumatoid arthritis (RA) is a relevant issue because of conflicting and consensus lacking reports published in literature. We investigated IL-6-174G > C promoter polymorphism in 34 RA patients, attending a tertiary care hospital in north India. We also performed a meta-analysis, of the previously published studies reporting this genetic relationship, in overall population, and independently in Asian and Caucasian ethnicities to further elucidate this association. A total of 13 studies, including the current one, involving 3291 RA cases and 3812 controls were analyzed. Out of the 13 studies, 6 were from Asian, 6 from Caucasian and 1 from a mixed population. Our case-control study showed significant association of IL-6-174G > C SNP with increased RA risk: allelic (OR = 3.750, 95% CI = 1.800–7.813, p < 0.001); dominant (OR = 2.800, 95% CI = 1.167–6.721, p = 0.021); and recessive (OR = 36.72, 95% CI = 2.004–672.7, p = 0.015). The meta-analysis revealed the increased RA risk associated with IL-6-174G > C SNP in overall population: allelic (OR = 1.650, 95% CI = 1.169–2.329, p = 0.004); homozygous (OR = 1.380, 95% CI = 0.906–2.101, p = 0.133); heterozygous (OR = 1.559, 95% CI = 1.001–2.428, p = 0.049); dominant (OR = 1.663, 95% CI = 1.078–2.567, p = 0.022); and recessive (OR = 1.366, 95% CI = 0.964–1.935, p = 0.079). Subgroup analysis also showed this polymorphism to be associated with increased RA risk in Asian population: allelic (OR = 3.724, 95% CI = 1.361–10.190, p = 0.010); dominant (OR = 3.823, 95% CI = 1.320–11.074, p = 0.013); and recessive (OR = 4.357, 95% CI = 1.634–11.623, p = 0.003), but not in Caucasian population. This meta-analysis shows that IL-6-174G > C SNP is significantly associated with increased RA risk in overall, and specifically in Asian population.